Representation, passage and consciousness of time - Toboso Martín, Mario (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In this article we carried out the analysis of the temporal categories that take part in time consciousness, and that form the categorial structure of the «field of presence» of the subject, which is not another thing that the above mentioned consciousness expressed as a field on such categories. We also treat on the phenomenon of the passage of time. We show its habitual ideation, based on the consideration of two different temporal movements. Its representation within the field of presence leads to interpret this phenomenon like the combination of both movements. Also, we introduce the difference between the «now» and the «present». The first one refers to the colloquial notion of time like «a line of nows», so that if we take any now on that line, we will have «before» (of that now) to its left and «after» to its right. On the other hand, the present is delimited by the categories «past» and «future». Finally, we explain how all these temporal elements are interlaced in a categorial and dynamical structure, the «Now».
Keywords: field of presence; phenomenology; temporal categories; passage of time; time consciousness